Blend films of pectin and bitter vetch (Vicia ervilia) proteins: Properties and effect of transglutaminase. (August 2016) - Porta, Raffaele; Di Pierro, Prospero; Sabbah, Mohammed; Regalado-Gonzales, Carlos; Mariniello, Loredana; Kadivar, Mahdi; Arabestani, Akram
Abstract: Hydrocolloid solutions were prepared by blending pectins and Vicia ervilia seed proteins at complexation pH and edible films were obtained by casting the solutions both in the absence and presence of microbial transglutaminase. Protein/pectin films exhibited a tensile strength double than the one observed with films containing only proteins, with an increase of about 3-fold observed in the presence of enzyme. Also the elongation at break resulted higher in the films containing transglutaminase, leading to conclude that films are more extensible mostly when both pectins and enzyme occur in the film forming solutions. A direct correlation between the improved film mechanical properties and the negative increase of zeta-potential of the originating film forming solutions was recorded. Conversely, gas permeability of protein/pectin films markedly decreased and transglutaminase addition determined a further enhancement of their barrier properties. These findings, supported by morphological analyses, suggest that the improved film functional features depend on their more compact structure due to crosslinked bitter vetch proteins grafted with pectin. Industrial relevance: The innovative packaging is becoming an important focus as food industries increasingly endeavor to reduce the environmental impact of their products. Biodegradable and/or edible materials made from renewable sources are interesting alternatives to produce ecofriendly food coatings being able to substitute petrochemical films and to reduce plastic wastes. Development of blended polysaccharide/protein-based biomaterials is an attractive option in the attempt of tuning biodegradable films endowed with tailored properties. In this study an improvement of bitter vetch protein edible films by pectin grafting and transglutaminase treatment is investigated. Graphical abstract: Highlights: Blends of proteins from Vicia ervilia and pectin produce films with properties better than those of the protein films alone Transglutaminase-mediated crosslinks improves film mechanical features and increases its gas barrier properties Crosslinks produced by transglutaminse affect film microstructure examined by AFM and SEM